Leonard Horner in Bonn 1831–1833, finding loess and being incorporated into Lyell’s Loess Legion - Smalley, Ian (Instytut Geologii UAM, 2020)
Leonard Horner (1785–1864) was a pioneer in the study of loess. His 1836 paper on the geology of Bonn contained detailed descriptions of loess in the Rhine valley. He identified and presented loess as an interesting material for geological study. He investigated loess in the crater of the Rodderberg with Charles Lyell in 1833. He presented the first significant paper on loess in Britain in 1833, but it was not published until 1836. With the assistance of G.A. Goldfuss and J.J. Noegerath he conducted early studies of the Siebengebirge and published the first geological map of the region, and the first picture of loess, at Rhondorf by the Drachenfels. He became the eleventh person to be included in the list of loess scholars which Charles Lyell published in volume 3 of the Principles of Geology. These were Leonhard, Bronn, Boue, Voltz, Steininger, Merian, Rozet, Hibbert in 1833, Noeggerath, von Meyer in 1835, Horner in 1837. Horner arrived after the publication of his studies on the loess at Bonn in 1836.
Keywords: Bonn; Siebengebirge; Rodderberg; loess first documentation